CYTOTOXICITY OF CURCUMIN, TAURINE AND ALPHA TOCOPHEROL ACETATE ON ZR-75-1 CELL LINE - Ramteke, Rupal; Moon, Archana; Taksande, Amit; Khan, Tuba; Salwankar, Rupal; Ansari, Mohd. Vashid (International Journal of Pharma and Bio Sciences, 2026)
Breast cancer continues to be one of the major contributors to cancer-related illness and death across the globe. Although current therapies are effective, they are often associated with significant side effects and invasive treatment protocols. This study explores the cytotoxic potential of three phytochemicals-Taurine, Alpha Tocopherol Acetate (α-TEA), and Curcumin-on ZR-75-1 human breast cancer cell lines, aiming to identify natural compounds that could serve as safer, adjunctive therapeutic options. Using the MTT assay, the effects of varying concentrations of each compound were assessed. Taurine and α-TEA exhibited cytotoxic effects at millimolar concentrations, while Curcumin demonstrated strong anticancer potential at low nanomolar concentrations. These findings support the role of phytochemicals in breast cancer treatment and underscore the need for further research into their mechanisms of action and therapeutic applicability